A-3 Cingulo-Opercular and Frontoparietal Control Network Connectivity and Executive Functioning in Older Adults. (30th August 2021) - Hausman, Hanna K; Hardcastle, Cheshire; Albizu, Alejandro; Kraft, Jessica N; Evangelista, Nicole D; Boutzoukas, Emanuel M; Langer, Kailey G; O'Shea, Andrew; Van Etten, Emily; Bharadwaj, Pradyumna K; Song, Hyun; Smith, Samantha G; et al.
Abstract: Objective: Executive functioning is a cognitive domain that typically declines with normal aging. Age-related disrupted connectivity in cingulo-opercular (CON) and frontoparietal control (FPCN) resting-state networks is associated with worse performance across various executive functioning tasks. This study examines the relationships between CON and FPCN connectivity and executive functioning performance in older adults across three subdomains: working memory, inhibition, and set-shifting. Methods: 274 healthy older adults (age M = 71.7, SD = 5.1; 87% Caucasian) from a clinical trial at the University of Florida and University of Arizona completed tasks of working memory (Digit Span Backwards [DSB]; Letter Number Sequencing [LNS]), inhibition (Stroop), and set-shifting (Trail Making Test Part B [TMT-B]). Participants underwent resting-state functional magnetic resonance imaging. CONN Toolbox (18b) was used for extracting average within-network connectivity of CON and FPCN. Multiple linear regressions were conducted with average network connectivity predicting performance, controlling for age, sex, education, and scanner. Results: Greater average CON connectivity was associated with better performance on DSB (β = 0.26, p < 0.001), LNS (β = 0.23, p < 0.001), Stroop (β = 0.24, p < 0.001), and TMT-B (β = −0.26, p < 0.001). Greater average FPCN connectivity was associated with better performance on DSB (β = 0.22, p < 0.001) and LNS (β = 0.18, p = 0.002). Conclusions: CON connectivity was significantly associated with working memory, inhibition, and set-shifting. FPCN connectivity was significantly associated with working memory. Future research should conduct regional connectivity analyses within these networks to identify intervention targets to improve executive functioning in older adults.